Faktor Risiko Dropout Kontrasepsi Suntik Progesteron - Nur Laila; Budiono Budiono; Sunarsih Sunarsih; Aditiawarman Aditiawarman (Universitas Airlangga, 2019)
Introduction: Prevention effort of progestogen-only prevalence rate injectable discontinuation has not got the national target and it always increases. The prevalence rate is one of causes Total Fertility Rate (TFR) increasing. The study analyzed the risk factors associated with the progestogen-only injectable discontinuation case.Methods: This study used analytic observational with cross sectional design which was carried out in Puskesmas Mojo Surabaya on March – April 2019. Population are 646 discontinuation acceptors and 5,751 non discontinuation acceptors of progestogen-only injectable. The inclusion criteria were acceptors of progestogen-only injectable discontinuation case, have a husband, not yet menopause. The exclusion criteria were acceptor of progestogen-only injectable discontinuation who used other contraception. Total samples are 44 samples obtained by with consecutive sampling. Independent variables were desire pregnancy, myths, weight change, spotting, amenorrhea, husband support. Dependent variable was the progestogen-only injectable discontinuation case. The data are collected by questionnaire, analyzed by chi-square test with α < 0.005 and multivariate analysis with independent variable p<0.25Results: The factor which correlated with the progestogen-only injectable discontinuation was husband support (p=0.012). The factors which not correlated with the case are desire pregnancy (p=1.000), myths (p=0.138), weight change (p=0.378), spotting (p=0.164), amenorrhea (p=0.192). The dominant factor was husband support (Odds Ratio = 26.571; 95%Cl = 2.497–282.736).Conclusion: The dominant factor in this study is husband support.